Tobacco and Nicotine Products Adverse Health Events: Findings From the FDA Safety Reporting Portal - Steven Alec Barrientos; Danny Dabroy; Mohammad Ebrahimi Kalan; Linnea Irina Laestadius; Ziyad Ben Taleb (SAGE Publishing, 2024)
Introduction The FDA oversees regulatory aspects of all U.S. tobacco products. Understanding the impact of emerging health trends and incidents associated with various tobacco and nicotine products is vital for public health. This study utilizes the FDA's Tobacco Product Problem Reports (TPPRs) to characterize and track adverse health events (AHEs) associated with tobacco and nicotine products over time, considering the impact of EVALI and the COVID-19 pandemic. Methods FDA TPPRs from 2017-2022 provided information on AHEs related to various tobacco products. After data cleaning, 839 reports were categorized by two independent coders based on affected health category, frequency of AHEs reports, and proportion of AHEs per each health category. Additionally, variations in AHEs over time were assessed, considering major health events like EVALI and the COVID-19 pandemic. Results Among the 839 reports, electronic cigarettes (e-cigarettes) were the primary product of concern, comprising 90.6% (n = 760) of all reports, surpassing traditional cigarettes (5.1%; n = 43) and other products. Notably, 45.6% of reports (n = 383) identified the neurological system as the most frequently mentioned health category, each reporting at least one AHE. This was followed by the respiratory (39.1%; n = 328) and digestive (10.7%; n = 90) systems. Among all reported AHEs, respiratory system issues were most frequent (25.9%; n = 512), closely followed by neurological (25.2%; n = 499) and digestive (6.6%; n = 131) concerns. Most reports occurred in 2019 (65.7%; n = 551), coinciding with the EVALI outbreak, with a subsequent decline post-Q3 2019, highlighting the potential impact of specific health crises on reporting trends. Conclusion E-cigarettes dominated adverse health reports, particularly affecting the neurological and respiratory systems, with a peak in 2019. Our findings provide insights to regulatory entities and future research, enhancing understanding of AHEs in lesser-explored bodily systems, such as the neurological and digestive systems. This study emphasizes the need for ongoing and improved surveillance of emerging tobacco products to protect public health.